1984
DOI: 10.1002/j.1460-2075.1984.tb02123.x
|View full text |Cite
|
Sign up to set email alerts
|

A 135-kd membrane protein of intercellular adherens junctions.

Abstract: We report here on a new 135-kd membrane protein which is specifically associated with intercellular adherens-type junctions. This surface component was identified by a monoclonal antibody, ID-7.2.3, raised against detergent-extracted components of membranes of chicken cardiac muscle rich in intercalated discs. The antibodies stain extensively adherens junctions in intact cardiac muscle and in lens, as well as in cultured cells derived from these tissues. In living cultured cells only very little immunolabellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
142
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(144 citation statements)
references
References 59 publications
2
142
0
Order By: Relevance
“…Cells were labeled using affinity purified R-851 antibodies and rhodamine-conjugated goat anti rabbit antibodies (Jackson Labs, Bar Harbor, ME) as described (Volk and Geiger, 1984).…”
Section: Immunofluorescence Labeling Of Cultured Cellsmentioning
confidence: 99%
“…Cells were labeled using affinity purified R-851 antibodies and rhodamine-conjugated goat anti rabbit antibodies (Jackson Labs, Bar Harbor, ME) as described (Volk and Geiger, 1984).…”
Section: Immunofluorescence Labeling Of Cultured Cellsmentioning
confidence: 99%
“…readily exchange with the cytoplasmic diffusible pool [Geiger et al, 1984;Kreis et al, 19851. This feature suggests that the assembly of the AJ complex and/or its modulation depends on the availability of potent binding sites for cytoplasmic junctional molecules at the endofacial surfaces of the junction itself rather than on an active and directional transport mechanism.…”
Section: Aj Dynamics and The Dilemma Of Subcellular Molecular Sortingmentioning
confidence: 99%
“…Early studies to search for the molecules responsible for the calcium-dependent junctions resulted in the identification of a group of type-I transmembrane proteins, and its founding member was termed cadherin (Yoshida and Takeichi 1982;Yoshida-Noro et al 1984). Related molecules identified were also called by various names, such as uvomorulin (Peyrieras et al 1983), LCAM (Gallin et al 1983), and ACAM (Volk and Geiger 1984). Later studies revealed that the cadherins form a superfamily, and therefore, the original cadherins are now called "classic" cadherins.…”
mentioning
confidence: 99%